Analisis Social Capital Pada Kemenangan Calon Bupati Independen Dalam Pilkada Kabupaten Aceh Besar Tahun 2024 - Hidayat, Amri Wahid; Lestari, Yeni Sri; Muliawati (Yayasan Sagita Akademia Maju, 2025)
The Regional Head Election (Pemilukada) in Indonesia, particularly in Aceh, has undergone significant changes with the emergence of independent candidates who are not affiliated with political parties. This study aims to analyze the existence of independent candidates in the Aceh Besar Pemilukada of 2024, focusing on the victory of the independent candidate pair, Muharram Idris and Syukri, who successfully garnered 33.8% of the votes, using social capital theory for analysis. This victory raises questions about the factors influencing their success amid fierce competition from candidates representing major political parties. Through a qualitative approach and case study method, this research collects primary data through interviews and observations, as well as secondary data from literature and media sources. The findings indicate that social capital, which includes networks, trust, and cooperation, plays a crucial role in supporting independent candidates. This study also highlights how the emergence of independent candidates reflects public dissatisfaction with nominations put forth by political parties, while providing an opportunity for the community to engage directly in the democratic process. These findings are expected to offer new insights into the dynamics of Pemilukada in Aceh and the contributions of independent candidates to the development of local democracy.